IMPLEMENTASI MODEL PEMBELAJARAN MULTIKULTURAL DI SEKOLAH DASAR PROPINSIDAERAHISTTMEWA YOGYAKARTA - Farida Hanum, Sisca Rahmadonna (Jurnal Penelitian Ilmu Pendidikan, 2010)
This research is aim to increase the children positive appreciation to the culturally differentiotion, as the based to increase the quality of teaching that give the safe, comfort and condusive situation to the children on the teaching and learning process. This research is the next application and development of the research result that success to develop the multicultural teaching and learning process in the elementary school student. The approach that is used in the whole research is research and development (R&D). The subject of the research is class teacher of 4th grade, the headmaster, the student, the elementary school committee, the official education in the Daerah Istimewa Yogyakarta province, that are choosed by purposive sampling. The data collection technique is questionnaire, observation, interview, and documentation study that support by the focus group discussion(FGD) and also the logbook. The data analysis is quantitative and qualitative descriptive. The results of the study are: (1) the modul for the students as the teaching resource supplement in the multicultural teaching on grade 4th; (2) teacher guidance on the multicultural teaching in the form of modul fot 4th grade; (3) the increase of the teacher ability on the multicultural teaching, especially in the 4th grade elementary school student; (4) the implementation of multiculture cultivation in the elementary school students. Keywords: Multicultural Teaching, Teaching Model, Teaching Modul